Pengembangan Kompetensi Sosial‑Emosional Anak Usia Dini :Pembelajaran Berbasis Bermain - Zamhariri, Muhammad Kharir (Maliki Interdisciplinary Journal, 2025)
Play is a crucial activity in early childhood development because it not only provides entertainment but also serves as a natural means of social-emotional learning. Through play, children learn to negotiate, control their emotions, and resolve simple conflicts, thereby further developing communication skills, independence, and self-confidence. Research by Mukhlis & Mbelo (2019) confirms that traditional games support five key aspects of Social Emotional Learning (SEL): self-awareness, self-management, social awareness, social skills, and responsible decision-making. In the context of holistic early childhood education (PAUD), play serves as a bridge for integrating physical, cognitive, social, moral, and emotional development, while strengthening cultural identity through values ​​of togetherness and sportsmanship. However, successful play-based learning requires emotionally sensitive teachers, capable of designing structured yet flexible activities, and the support of the learning environment and parents. This article aims to describe the contribution of play to the social-emotional development of early childhood in Islamic PAUD